Analisis Perbandingan Pengungkapan Laporan Keberlanjutan Industri Perbankan Bumn di Indonesia Sebelum Dan Selama Pandemi Covid-19 Berdasarkan Global Reporting Initiative Index - Hariara Daniel Parlindungan; Affandy, Didied Poernawan (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to compare the disclosures and Sustainability Reports of BNI, BRI, and BTN based on the 2016 GRI Standards, both general and specific disclosures, in 2019 and 2020. The data in this study were analyzed descriptively. The results exhibited that the total percentage of disclosure in the 2019 and 2020 Sustainability Reports for the three banks meagerly increased. In addition, the 2016 GRI index disclosed and reported in the 2020 Sustainability Report was higher than that in 2019 with relatively similar disclosed and reported specific topics. This study also proves that the results of previous studies by Rahayu (2019) and Sahla & Aliyah (2016) are confirmed. On the other hand, inaccuracies in the use of the GRI index were found in the Sustainability Report, both in 2019 and 2020.